A comparison of sleep patterns in youth soccer players and non-athletes. Issue 1 (2nd January 2018) - Whitworth-Turner, Craig; Di Michele, Rocco; Muir, Ian; Gregson, Warren; Drust, Barry
ABSTRACT: The current study compared sleep characteristics of youth soccer players ( N = 12, 19 ± 1 years) with non-athletes ( N =12, 23 ± 3 years) over a period of six nights using a wireless electroencephalogram sleep monitor. This device provided a breakdown of the participant's sleep schedule, sleep latency, sleep duration and awakenings. Participant mean and SD were calculated across the six nights to form the between group comparisons (i.e., independent t -tests, Mann–Whitney–Wilcoxontests and effect sizes [ESs]). The youth soccer players displayed longer sleep durations than the non-athletes (+64 min; ES: 1.39; P < 0.05), which may relate to a later time of final awakening (+67 min; ES: 1.60; P < 0.05). This may have resulted from the timing of activities associated with the imposed soccer schedule, highlighting the importance of externally derived schedules in facilitating sleep quantity. Despite longer sleep durations, the youth soccer players displayed longer sleep latency (+10 min; ES: 1.00; P < 0.05), lowered sleep efficiency (−3%; ES: 1.09; P < 0.05) and higher intraindividual variability for both variables. Such factors suggest a greater prevalence of sleep disruption in youth soccer players, which may warrant the use of tailored sleep hygiene strategies.